Simultaneously efficient adsorption and photocatalytic degradation of tetracycline by Fe-based MOFs - Wang, Dongbo; Jia, Feiyue; Wang, Hou; Chen, Fei; Fang, Ying; Dong, Wenbo; Zeng, Guangming; Li, Xiaoming; Yang, Qi; Yuan, Xingzhong (Journal of colloid and interface science, 2018)
[Display omitted] Recently, Fe-based metal–organic frameworks (MOFs) have attracted increasing attention and been widely used. To date, however, it is unknown whether they can be employed to degrade tetracycline, one of the most widely used antibiotics. This work therefore aims to provide such support by comparing the performance of three Fe-based MOFs (namely, Fe-MIL-101, Fe-MIL-100, and Fe-MIL-53) in removing tetracycline. Experimental results showed that Fe-MIL-101 exhibited the best performance in tetracycline removal, with 96.6% of tetracycline being removed (initial tetracycline concentration at 50 mg/L) while Fe-MIL-100 and Fe-MIL-53 removed 57.4% and 40.6% under the same conditions. Additionally, the effects of adding dosage, adsorption time, and initial concentration of tetracycline on degradation efficiency were examined. It was found that the adsorption and photocatalytic degradation effect was better with the increase of time, the optimum dosage of Fe-MIL-101 was 0.5 g/L and the removal efficiency decreased with the increasing of initial tetracycline concentrations. Moreover, the trapping experiments and ESR tests indicated that O2−, OH and h+ were the main active species in photocatalytic degradation process of tetracycline. Due to its high removal efficiency and simple synthesis, it could be used as a potential catalyst for degradation of tetracycline and other antibiotics.